New Methods and Ways of Foreign Language Teaching (Eurasian Journal of Research, Development and Innovation, 2021)
The article provides information on new methods of foreign language teaching, as well as ideas for new materials and methods used in foreign language teaching. In addition, these methods were analyzed using examples.